Psychological Well-Being dan Work Engagement Karyawan CV Sentosa Abadi Morowali, Sulawesi Tengah - Frolis Labiro; Happy Cahyani Sunusi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The purpose of this study was to examine the relationship between psychological well-being and employee work engagement at CV Sentosa Abadi. This research approach uses a quantitative method with 108 employees as research subjects with the criteria of employees who are still working at CV Sentosa Abadi for at least 6 months. The data collection tool used PWB-18 questionnaire and UWES-9 questionnaire while data analysis used the Spearman Rank correlation test with a p-value ≤ 0.05. The results showed that 70 employees were in the moderate category for psychological well-being and 51 employees were in the very high category for work engagement. The results of the correlation test showed that the relationship between psychological well-being and work engagement was 0.492 in the fairly strong category with a p-value of 0.000000059 ≤ 0.05, which means there is a significant relationship between the two variables. The higher the psychological well-being so the higher the employee's work engagement and so does the opposite.